Comparative machining studies on custom 450 alloy with TiCN, TiAlN coated and uncoated carbide tools using Taguchi-Fuzzy logic approach. (22nd March 2019) - Kumar, T Sampath; Ramanujam, R; Vignesh, M; Rohith, Dunna; Manoj, Vavilapalli; Sankar, Peddi Hema
Abstract: In this study, the comparative performance evaluation of PVD (Physical Vapour Deposition) coated TiCN, TiAlN and uncoated cemented carbide inserts are investigated in machining of Custom450 stainless steel as the workpiece material. The experimental work is carried out on CNC (Computerized Numerical Control) turning machine by varying cutting speed, feed rate and depth of cut according to Taguchi's L9 orthogonal array design. The output responses such as tool wear, surface roughness, cutting forces, tool temperature and chip formation were analyzed using S/N ratio, ANOVA (Analysis of Variance). The fuzzy logical network is used to predict the optimal levels by converting the multiple responses into a single response output. The mean response graphs are plotted based on the COM value obtained from the fuzzy logic approach. The cutting speed of 100 m min −1, the feed rate of 0.14 mm/rev and depth of cut of 0.25 mm was obtained as optimized machining conditions for TiCN coated carbide tool. The TiCN coated tool has higher parametric contribution given by cutting speed, followed by feed rate and the least contribution by the depth of cut. This is followed by an intermediate contribution of cutting speed and lower contribution by the depth of cut based on the ANOVA results obtained for COM values. The machining studies have shown that the TiCN coated tool has obtained improved performance, when related to TiAlN coated and uncoated cemented carbide cutting tools.